Approaching Reading from the Perspective of the Ministry of Education and the Dialogic Pedagogy “Enlazando Mundos” - Del Pino-Sepúlveda, Miguel (2016)
This research aims to characterize the curriculum, the didactics and the assessment promoted by the Ministry of Education of Chili, and the dialogic pedagogy “Enlazando Mundos” (Bridging Worlds). This is a qualitative study based on the dialogic-Kishu Kimkelay Ta Che research approach, with a design of two case studies derived from documentary sources. The procedure to collect and construct knowledge is the interpretation of the dialogic speech; as a data analysis, it focuses on pedagogical definitions from the perspective of transformative, excluding and conservative dimensions, in order to compare-interpret and reflect on educational inputs in relation to reading in a course of language and communication. As a result, it is observed the incongruity from the State in communicative curriculum design and its operational proposal, and in the regionalized construction the dialogic pedagogy “Enlazando Mundos” (Bridging Worlds) is carrying out.